Efficient adsorption of europium (III) and uranium (VI) by titanate nanorings: Insights into radioactive metal species - Zheng, Maosheng; Ji, Haodong; Duan, Jun; Dang, Chenyuan; Xingmin Chen; Liu, Wen (Environmental Science and Ecotechnology, 2020)
Radioactive wastewater containing high concentration of radionuclides poses severe threats to ecosystem and human health, so efficient removal of these toxic heavy metals is urgently needed. Titanate nanomaterials have been demonstrated good adsorbents for heavy metals due to ion exchange property. In this study, titanate nanorings (TNRs) were synthesized using the facile hydrothermal-cooling method. The TNRs were composed of sodium trititanate, with a chemical formula of Na0.66H1.34Ti3O7•0.27H2O and a Na content of 2.38 mmol/g. The TNRs demonstrated sufficient adsorption performance to radionuclides europium (Eu) and uranium (U) ions. Specifically, even at a high initial concentration of 50 mg/L, 86.5% and 92.6% of the two metal ions can be rapidly adsorbed by the TNRs within 5 min, and equilibrium was reached within 60 min at pH 5. The maximum adsorption capacity (Qmax) obtained by the Langmuir isotherm model was 115.3 mg/g for Eu(III) and 282.5 mg/g for uranium U(VI) at pH 5, respectively. The adsorption capacities of the two metals under various water chemical conditions were highly related to their species. Ion exchange between metal cations and Na+ in the TNR interlayers was the dominant adsorption mechanism, and adsorption of U(VI) was more complicated because of the co-existence of various uranyl (UO22+) and uranyl-hydroxyl species. The spent TNRs were effectively regenerated through an acid-base or ethylenediamine tetraacetic acid (EDTA) treatment and reused. Considering the large adsorption capacity and quick kinetic, TNRs are promising materials to remove radionuclides in environmental purification applications, especially emergent treatment of leaked radionuclides.
Keywords: Adsorption; Ion exchange; Radionuclides; Species; Titanate nanorings